Performing the encounter; a practice-led inquiry - Luppes, Juliette (Centre for Film and Media Studies, 2025)
This dissertation explores the ethical and relational dimensions of verbatim theatre, focusing on how encounters between theatre-makers, participants, and audiences shape both the creative process and the final performance. Moving beyond traditional notions of representation, it argues that verbatim theatre is not merely a vehicle for reproducing real-life narratives but a dynamic practice of engagement, wit(h)nessing, and artistry. Through a practice-led inquiry, two key projects - Sense of Home and Company in the Gardens - are examined to consider how verbatim theatre can foster attentiveness to the complexities of lived experience while avoiding ethical paralysis in creative work with real-life narratives. By prioritising the process of encounter over fixed notions of truth or authenticity, these projects explore how the exchange between interviewer and interviewee, performer and audience, generates meaning and challenges pre-existing assumptions. The research situates verbatim theatre within broader discussions on ethics, presence, and relationality, considering how the form can resist simplification, create spaces for dialogue, and foster meaningful connections across difference. By weaving together autoethnographic reflections, theoretical analysis, and artistic practice, this study proposes a framework for an ethical and relational approach to verbatim theatre. Ultimately, it positions the form as a political act - an ongoing practice of presence, attentiveness, and shared meaning-making.